The effects of surprise political events on quoted firms: The March 2004 election in Spain - Pau Castells; Francesc Trillas (SERIEs - Journal of the Spanish Economic Association, 2013)
In the last days of the electoral campaign for the 2004 general election in Spain, on Thursday March 11th 2004, a series of simultaneous terror attacks caused the death of 191 persons in commuting trains in the capital Madrid. Four days later, the opposition party won the election, against all predictions that were made prior to the terror attacks. This change in expectations presents a unique opportunity to take advantage of event study techniques to test some politico-economic hypotheses. The quantitative exercise is carried out employing Seemingly Unrelated Regressions (SUR). Hypothesis testing is improved by means of bootstrapping techniques. Convergence theories prove quite resilient as, jointly, quoted firms were not significantly affected by the election outcome. The impact on politically connected companies and particular economic sectors, however, suggest that a combination of capture and agency problems may play a role in explaining the effects of the change in expectations.
Keywords: G14; G15; 330; event study; median voter; agency; capture; elections; political connections